Implementasi Pendekatan Kontekstual Teaching and Learning dalam Pendidikan Agama Islam - Ikrima Mailani (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2019)
Abstract Educators are very important in their efforts to achieve the desired learning goals in the activities of the teaching and learning process. While students act as subjects as well as objects in applying contextual teaching and learning learning methods. Various ways can be done by the teacher to be able to convey information to students (knowledge transfer), both in the form of learning related to teaching materials or insightful ones globally. The process of transferring knowledge with conventional methods can no longer be maintained, because students who are expected by the community are intelligent students who are responsive to the development of the times, and not just as spectators and listeners. The breakthrough offered by observers of education is with a new concept of contextual teaching or learning (CTL), the contextual learning method is not just a process of transferring knowledge from teacher to student, but students can do, try and reconstruct the teaching material themselves obtained from the teacher and correlated in the real life of students, with the hope that they can solve various problems both in themselves, their families and society. Keywords: Methods, Contextual Teaching and Learning, Islamic Education